Antioxidant and antimicrobial properties of Litsea elliptica Blume and Litsea resinosa Blume (Lauraceae) - Mui Hung, Wong; Li Fang, Lim; Fasihuddin Badruddin, Ahmad; Zaini, Assim (Asian Pacific Journal of Tropical Biomedicine, 2014)
Objective: To investigate antioxidant and antimicrobial activities of two plant species, Litsea elliptica (L. elliptica) and Litsea resinosa (L. resinosa). Methods: In vitro method -2,2-diphenyl-1-picrylhydrazyl radical scavenging assay was cdoifnfudsuicotne da sfsoary a anntido xmidyacnetl iaalc triavditiya ld gertoewrmthi naastsiaoyn. while antimicrobial assay consisted of agar well Results: Methanol extracts of root and stem of L. elliptica and L. resinosa exhibited the highest eaxnttriaocxtisd aonf tL a. crteisviintyo swa itahs EwCel50l oafs 2r3o.o9t9,e x41tr.a6c9,t s1 1fr.o22m aLn.d e 3ll5i.p4t8ic ma gs/hLo wreesdp escigtinviefilcya. nAt lsl cmaveethnagninogl nacetgiavtiitvye. Hbeaxcatenrei ae xPtsreauctd ofrmomon astse mae rouf gLi.n oressai naonsda Eprsecsheenritcehdi ath ceo llai rwgehsitl ei nchhilboirtoiofonr mzo neex tirna cGt rfarmom- inner bark of L. resinosa showed major inhibition towards Gram-positive bacteria Bacillus subtilis. Essential oils from the root of both species showed significant antifungal activities which are 80.11% and 66.85% respectively. Conclusions: Overall, methanol extracts from root and stem of both species showed antioxidant satcrtoinvigteyr c aonmtipmaircarbolbei atol pstraonpdeartride sb cuotymlaptaerde dh ytod rtohxayt tforloumen Le.. eEllxitprtaiccats.